2000
DOI: 10.1016/s0006-3495(00)76670-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Voltage Drop within the Synaptic Cleft on the Current and Voltage Generated at a Single Synapse

Abstract: In a model of a single synapse with a circular contact zone and a single concentric zone containing receptor-gated channels, we studied the dependence of the synaptic current on the synaptic cleft width and on the relative size of the receptor zone. During synaptic excitation, the extracellular current entered the cleft and flowed into the postsynaptic cell through receptor channels distributed homogeneously over the receptor zone. The membrane potential and channel currents were smaller toward the cleft cente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
40
0
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 24 publications
(44 citation statements)
references
References 29 publications
3
40
0
1
Order By: Relevance
“…However, a recent theoretical investigation suggested that narrowing the cleft could significantly increase the effective cleft resistance. thus reducing the synaptic current (24), in line with the classical conjecture by Eccles (23). The present study investigates how these two phenomena interact, concluding that the synaptic cleft height may have an adaptive function of optimizing synaptic strength.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…However, a recent theoretical investigation suggested that narrowing the cleft could significantly increase the effective cleft resistance. thus reducing the synaptic current (24), in line with the classical conjecture by Eccles (23). The present study investigates how these two phenomena interact, concluding that the synaptic cleft height may have an adaptive function of optimizing synaptic strength.…”
Section: Discussionsupporting
confidence: 87%
“…A similar phenomenon has been proposed to occur in central synapses (24). Could this counterbalance the effects of the increased neurotransmitter concentration in narrow clefts?…”
supporting
confidence: 52%
See 2 more Smart Citations
“…For the sake of simplicity we choose a model which combines the two processes: We consider a reversible binding-release reaction of ion channels with the cell skeleton and assume that this interaction induces a closing of the channels. Alternative models for pattern formation along the cell membrane take additional intermediate steps of the opening-closing dynamics into account [18,22,23,33] but a thorough analysis of the pattern formation processes in two spatial dimensions is not available yet.…”
Section: Introductionmentioning
confidence: 99%